Fathers’ Criminal Behavior and Involvement With Children: The Moderating Role of Family Relationships - Charles, Pajarita (J Soc Social Work Res, 2018)
OBJECTIVE: Research indicates that fathers’ criminal behavior can be problematic for children through multiple pathways, yet few studies have examined the effect of fathers’ kinship networks in this process. This study examines the association between fathers’ criminal behavior and involvement with their children and the extent to which a father’s relationships with individuals in his extended family network moderate this association. METHOD: Hierarchical linear modeling was used to predict fathers’ involvement using data from a longitudinal intergenerational study of 335 children and 149 low-income, minority fathers. Measures included 8 father-involvement outcomes, a measure of fathers’ criminal behavior, and 2 moderator variables. RESULTS: High-quality relationships between fathers and their male relatives moderated the negative effect of criminal behavior on measures of fathers’ involvement. Criminal behavior was only associated with decreasing levels of father involvement when fathers had low-quality relationships with male relatives. CONCLUSIONS: Strong and affirmative relationships—with male relatives specifically—may attenuate the adverse effects of antisocial and criminal behavior on fathers’ involvement in at-risk families. Implications for tailoring practice to improve relationships between fathers and male relatives and to enhance fathers’ prosocial involvement are noted.